Proceedings of the 2018 ACM International Conference on Interactive Surfaces and Spaces 2018
DOI: 10.1145/3279778.3279782
|View full text |Cite
|
Sign up to set email alerts
|

Post-meeting Curation of Whiteboard Content Captured with Mobile Devices

Abstract: The traditional dry-erase whiteboard is a ubiquitous tool in the workplace, particularly in collaborative meeting spaces. Recent studies show that meeting participants commonly capture whiteboard content using integrated cameras on mobile devices such as smartphones or tablets. Yet, little is known about how people curate or use such whiteboard photographs after meetings, or how their curation practices relate to post-meeting actions. To better understand these postmeeting activities, we conducted a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, it does not facilitate remote collaboration, and material written on traditional whiteboards cannot be kept and shared digitally. Several studies [48][49][50] are devoted to the digitization of whiteboard material. Refs.…”
Section: Natural Interface and Collaborative Whiteboardsmentioning
confidence: 99%
“…However, it does not facilitate remote collaboration, and material written on traditional whiteboards cannot be kept and shared digitally. Several studies [48][49][50] are devoted to the digitization of whiteboard material. Refs.…”
Section: Natural Interface and Collaborative Whiteboardsmentioning
confidence: 99%
“…As was shown in the discussion before, multimodal features of WhatsApp were increasingly utilized by the students as an affordance to expand their agency. Recent studies showed that taking pictures of writings on the board using smartphones was the current norm for the students (Klokmose & Bertelsen, 2013;Varona-Marin, 2016). Hence, this phenomenon was not a new practice, and they might have done that long before using WhatsApp, to save time and to be able to focus more attention on what the teachers were saying.…”
Section: Multimodal Activitymentioning
confidence: 99%